Pathogen detection on microfluidic platforms: Recent advances, challenges, and prospects - Jagannath, Akshaya; Cong, Hengji; Hassan, Jaythoon; Gonzalez, Gabriel; Gilchrist, Michael D.; Zhang, Nan (Biosensors and bioelectronics. X, 2022)
Point-Of-Care (POC) testing has advanced to more affordable and rapid alternatives by adapting conventional immunoassays and molecular assays (isothermal amplification, CRISPR, digital and real-time quantitative PCR) on polymeric and paper microfluidic platforms. However, commercialization of these POC devices often depends on tackling long-term challenges in performing conventional tests on novel platforms including contamination, assay sensitivity, accurate signal detection, minimizing manual handling, and instrumentation. This review presents recent advances in detection techniques (immunoassays and molecular assays on microfluidic platforms) and aids for improving detection throughput. Various prospects for sustainable pathogen detection and future developments for commercial viability in the field of rapid diagnostics are also discussed. •Compatible and challenging aspects of individual assay methods are important for adapting to microfluidic platforms.•Leveraging novel microenvironments for pathogen detection helps minimize contamination and stability issues.•Combining detection methods improves assay sensitivity; multiplex-friendly microfluidic chip designs improve efficiency.